2022
DOI: 10.53730/ijhs.v6ns5.11275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of terpenes fraction of Iraqi cicer arietinum in experimentally induced hyperlipidemic mice

Abstract: The aim of this study is to investigate the antihyperlipidimic effect of Terpenes fraction of Iraqi Cicer areitinum in high-fat diet (HFD)-fed mice. Animals were divided into four groups (n =8). The total duration of the study was 56 days split into two intervals. During the first 28-days interval, mice were administered with HFD, whereas during the second 28-days interval they were co-administered HFD plus Terpenes (500mg/kg: p.o.) or the standard drug Atorvastatin (10mg/kg:p.o.). Terpenes treatment to HFD-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…The results of this study support previous findings on the potent effects of the phenolic fraction on protein expression. Consistent with the research by Vakili et al and Salam et al that indicated the crucial effect of phenolic substances is due to their ability to impede the progression of cancer 20,21 by enhancing the expression of p53, which © 2023 the authors. This work is licensed under the Creative Commons Attribution 4.0 International License activates pro-apoptotic factors and inhibits anti-apoptotic activity, as well as by preventing the activity of telomerase enzymes.…”
Section: Resultssupporting
confidence: 86%
“…The results of this study support previous findings on the potent effects of the phenolic fraction on protein expression. Consistent with the research by Vakili et al and Salam et al that indicated the crucial effect of phenolic substances is due to their ability to impede the progression of cancer 20,21 by enhancing the expression of p53, which © 2023 the authors. This work is licensed under the Creative Commons Attribution 4.0 International License activates pro-apoptotic factors and inhibits anti-apoptotic activity, as well as by preventing the activity of telomerase enzymes.…”
Section: Resultssupporting
confidence: 86%